2001
DOI: 10.1091/mbc.12.9.2730
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Smooth Muscle Actin Expression Upregulates Fibroblast Contractile Activity

Abstract: To evaluate whether ␣-smooth muscle actin (␣-SMA) plays a role in fibroblast contractility, we first compared the contractile activity of rat subcutaneous fibroblasts (SCFs), expressing low levels of ␣-SMA, with that of lung fibroblasts (LFs), expressing high levels of ␣-SMA, with the use of silicone substrates of different stiffness degrees. On medium stiffness substrates the percentage of cells producing wrinkles was similar to that of ␣-SMA-positive cells in each fibroblast population. On high stiffness sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

47
947
3
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,114 publications
(1,018 citation statements)
references
References 65 publications
47
947
3
4
Order By: Relevance
“…64,65 Herein, we have demonstrated that overexpression of a constitutively active T␤RI mutant improved the motility of aged cardiac fibroblasts but not their ability to contract collagen pads (Figure 4). Myofibroblast maturation and migration are the opposite spectra of T␤R-mediated responses; expression of ␣-SMA increases fibroblast contractile activity 66 and decreases fibroblast motility. 67 Clearly, overexpression of T␤RI promoted the actin cytoskeleton reorganization required for directed migration 68 and, therefore, partially rescued the functioning of aged fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…64,65 Herein, we have demonstrated that overexpression of a constitutively active T␤RI mutant improved the motility of aged cardiac fibroblasts but not their ability to contract collagen pads (Figure 4). Myofibroblast maturation and migration are the opposite spectra of T␤R-mediated responses; expression of ␣-SMA increases fibroblast contractile activity 66 and decreases fibroblast motility. 67 Clearly, overexpression of T␤RI promoted the actin cytoskeleton reorganization required for directed migration 68 and, therefore, partially rescued the functioning of aged fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…To identify single contractile cells, stably transduced sh-cont and sh-qkI HITA2 VSMCs or VSMCs overexpressing enhanced green fluorescent protein (EGFP), MYOCD-v1a, MYOCD-v1b, MYOCD-v3a, or MYOCD-v3b were seeded on deformable silicone substrates (stiffness 5 kPa; Excellness Biotech, Lausanne, Switzerland) 29 in M199 culture medium containing 1% FCS. Cells were seeded onto substrates coated with 10 µg/mL fibronectin isolated from human plasma.…”
Section: Functional Assessment Of Vsmc Contractilitymentioning
confidence: 99%
“…Using deformable silicone substrates and a three dimensional collagen lattice, a correlation between α-SMA expression level and fibroblast contraction force was found. In addition, fibroblasts transfected with α-SMA cDNA had increased contractile ability [Hinz et al, 2001]. …”
mentioning
confidence: 99%